Cold Physical Plasma in Cancer Therapy: Mechanisms, Signaling, and Immunity. (24th December 2021) - Faramarzi, Fatemeh; Zafari, Parisa; Alimohammadi, Mina; Moonesi, Mohammadreza; Rafiei, Alireza; Bekeschus, Sander
Abstract : Despite recent advances in therapy, cancer still is a devastating and life-threatening disease, motivating novel research lines in oncology. Cold physical plasma, a partially ionized gas, is a new modality in cancer research. Physical plasma produces various physicochemical factors, primarily reactive oxygen and nitrogen species (ROS/RNS), causing cancer cell death when supplied at supraphysiological concentrations. This review outlines the biomedical consequences of plasma treatment in experimental cancer therapy, including cell death modalities. It also summarizes current knowledge on intracellular signaling pathways triggered by plasma treatment to induce cancer cell death. Besides the inactivation of tumor cells, an equally important aspect is the inflammatory context in which cell death occurs to suppress or promote the responses of immune cells. This is mainly governed by the release of damage-associated molecular patterns (DAMPs) to provoke immunogenic cancer cell death (ICD) that, in turn, activates cells of the innate immune system to promote adaptive antitumor immunity. The pivotal role of the immune system in cancer treatment, in general, is highlighted by many clinical trials and success stories on using checkpoint immunotherapy. Hence, the potential of plasma treatment to induce ICD in tumor cells to promote immunity targeting cancer lesions systemically is also discussed.